Percutaneous vertebroplasty: a comparison between the procedure using the traditional and the new side-opening cannula for osteoporotic vertebral fracture Vertebroplastia percutânea: uma comparação entre o procedimento usando a cânula tradicional e a nova cânula de orifício lateral para fratura vertebral osteoporótica - Nicandro Figueiredo; Filipe Barra; Laryssa Moraes; Roger Rotta; Luiz Augusto Casulari (Arquivos de Neuro-Psiquiatria)
A total of 47 percutaneous vertebroplasties (PVs) were performed for osteoporotic vertebral fractures in 31 patients, 25 PVs were performed using the frontal-opening cannula (FOC) and 22 using the new side-opening cannula (SOC), randomly distributed. The incidence of cement extrusion was 27% with the SOC, and 68% with the FOC, all asymptomatic (p<0.01). The pain control was similar for both groups, with good improvement of pain in most of the patients, and there were no clinical relevant complications. The cement leakage can be significantly reduced with this new SOC, which allows for a better cement injection toward the center of the vertebral body, increasing the safety of the procedure, with no increase in cost. Um total de 47 vertebroplastias percutâneas (VP) foram realizadas para fraturas vertebrais osteoporóticas em 31 pacientes, 25 VP foram realizadas usando-se a cânula de orifício frontal (COF) e 22 com a nova cânula de orifício lateral (COL), distribuídos randomicamente. A incidência de extrusão de cimento ortopédico ocorreu em 27% com a COL, e 68% com a COF, todas assintomáticas (p<0,01). O controle da dor foi similar em ambos os grupos, com boa melhora da dor na maioria dos pacientes, sem complicações clínicas relevantes. A extrusão do cimento pode ser significativamente reduzida com esta nova COL, que permite uma melhor injeção do cimento para o centro do corpo vertebral, aumentando a segurança do procedimento, sem aumento no seu custo.